2018
DOI: 10.1016/j.scitotenv.2017.11.126
|View full text |Cite
|
Sign up to set email alerts
|

Blood mercury, lead and cadmium levels and determinants of exposure among newcomer South and East Asian women of reproductive age living in Vancouver, Canada

Abstract: Asian women recently arrived in Vancouver had higher blood Hg, Pb and Cd concentrations than same-age Canadian women measured in a national survey. Among South Asian newcomer women of reproductive age, exposure to Cd may continue after arrival. Local exposures to Hg occur through seafood and potentially through ingestion of imported traditional remedies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 40 publications
1
28
3
Order By: Relevance
“…A rather unexpected finding was the complete lack of association between dietary habits and erythrocyte lead concentrations. While diet is commonly not seen as a primary source of lead in the general population, previous reports suggested that some foods or food groups may play a role, for instance fish and shellfish [26] or dairy products [27]. Instead, none of these associations was confirmed in adjusted analyses in our study, neither in the total study sample, nor in any of the subgroup analyses (including never smokers).…”
Section: Discussioncontrasting
confidence: 92%
“…A rather unexpected finding was the complete lack of association between dietary habits and erythrocyte lead concentrations. While diet is commonly not seen as a primary source of lead in the general population, previous reports suggested that some foods or food groups may play a role, for instance fish and shellfish [26] or dairy products [27]. Instead, none of these associations was confirmed in adjusted analyses in our study, neither in the total study sample, nor in any of the subgroup analyses (including never smokers).…”
Section: Discussioncontrasting
confidence: 92%
“…Calcium, of which milk and other dairy products are a major dietary source, is a low affinity inhibitor of DMT1 activity [62] and so a diet that is high in calcium might be expected to lower B-Cd. We found no association of B-Cd with the frequency of drinking milk or with calcium intake, although a previous study of East and South Asian women of reproductive age who had recently immigrated to Canada (≤5 years) found that higher dairy product consumption was associated with a 14% lower risk of elevated B-Cd [63]. In addition, increasing dietary calcium and vitamin D in pregnant women also in Canada was associated with lower B-Cd [64].…”
Section: Discussioncontrasting
confidence: 88%
“…In addition, increasing dietary calcium and vitamin D in pregnant women also in Canada was associated with lower B-Cd [64]. The disparity between our study and these two studies could be accounted for by differences in the mean frequency of milk/dairy consumption, but comparison is difficult because of differences in the way in which variables are expressed [63] included data on the consumption of dairy items (52 ± 34 times/month); the present UK study included data specifically for milk (44% never or rarely consumed milk, 48% had 7-14 glasses per week, and 9% had ≥21 glasses per week). The disparity in the results could also indicate differences in the frequency of consumption of other foods and food groups, which could have a secondary effect on both dietary intake and absorption of Cd.…”
Section: Discussioncontrasting
confidence: 72%
“…52 Its level increased in accordance with the number of dental amalgam fillings in the children, as well as the consumption of marine and fish products. 53 On average, the levels of Hg in the body of the screened persons did not exceed the recommended values.…”
Section: Mercury Levels In Blood and Urinementioning
confidence: 89%